STRATEGI BRAND COMMUNICATION DALAM PENGUATAN BRAND AWARENESS PARIWISATA KABUPATEN BLITAR: (Studi Pada Program OLAS KEMBAR KEMBAR) - Andiwi Meifilina (Universitas Islam Balitar, 2020)
The existence of competition between products in the field of toursm is very important to increase brand communication in the program inmaintaining loyal consumers. Creating regulercustomers who are loyal and loyal to the products is what the agency or agency wants in making strategy an marketing in an effort to make customers who are certainly interested in participating in this program regularly on products or services from the company. The research uses a case study approach and this type of research is the qualitative. This research uses the Non Positivsm/ Naturalistic/ Interpretative paradigm or commonly called the qualitative paradigm. Promotiom board is a very important marketing strategy for improving the tourism sector. The brand communication strategy activities include the following: a). New Brand, b). Line Extension, c). Brand Extension. As forbrand awareness in the OLAS KEMBAR (don’t go anywhere before visiting Blitar) program by the Blitar District Regional Tourism Promotion Board. Toursm in Blitar district can be built and improved through the following methods: a). The message of the OLAS KEMBAR program delivered by a brand, is only remembered by consumers. b). The message delivered by the OLAS KEMBAR program must be different from other product brands and there must be a reletationship between brands and product categories. c). The program uses catchy song slogans and jinles, so helping consumers remember the brand, d). The program has a symbol, it should be associated with their symbol, e). The expansion of the program can be used so that the brand can be remembered by customers, f). Brand awareness in the program can be strengthened by using a gesture that fits the category, product, brand or both, g). The program makes repetition to strengthen memories because forming memories is more difficult than forming identities. By using this marketing strategy there has been increase in the number of tourist visits and an increase in the tourism sector and the economy in Blitar which is quite significant so that evaluation and monitoring of this program must continue to be carried out by the relevant agencies.